2022
DOI: 10.2147/ijgm.s342917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gefitinib Combined with Chemotherapy in Patients with Advanced NSCLC: A Retrospective Cohort Study

Abstract: Background There are currently no methods for the treatment of reversible drug-resistant EGFR-TKI lung cancer in the clinical setting, and thus, the patients finally return to the currently used drugs. This study aimed to compare the efficacy of chemotherapy alone and gefitinib combined with chemotherapy in the treatment of non-small cell lung cancer (NSCLC) patients in advanced stage with the mutation of epidermal growth factor receptor (EGFR). Methods A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…However, the recent retrospective cohort investigation carried out by Dai and colleagues in 2022 that solely focused on the influence of gefitinib when administered in combination with conventional chemotherapeutic agents in advanced NSCLC corroborated our study results [24]. This particular investigation analyzed therapeutic outcomes within a total of 120 clinical cases of advanced EGFR mutation-positive NSCLC across two separate cohorts control cohort (CC) -treated with conventional chemotherapy alone; observation cohort (OC) -treated with conventional chemotherapy + gefitinib [24].…”
Section: Gefitinib Overall Safety Profile/quality-of-life Extensionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the recent retrospective cohort investigation carried out by Dai and colleagues in 2022 that solely focused on the influence of gefitinib when administered in combination with conventional chemotherapeutic agents in advanced NSCLC corroborated our study results [24]. This particular investigation analyzed therapeutic outcomes within a total of 120 clinical cases of advanced EGFR mutation-positive NSCLC across two separate cohorts control cohort (CC) -treated with conventional chemotherapy alone; observation cohort (OC) -treated with conventional chemotherapy + gefitinib [24].…”
Section: Gefitinib Overall Safety Profile/quality-of-life Extensionsupporting
confidence: 90%
“…However, the recent retrospective cohort investigation carried out by Dai and colleagues in 2022 that solely focused on the influence of gefitinib when administered in combination with conventional chemotherapeutic agents in advanced NSCLC corroborated our study results [24]. This particular investigation analyzed therapeutic outcomes within a total of 120 clinical cases of advanced EGFR mutation-positive NSCLC across two separate cohorts control cohort (CC) -treated with conventional chemotherapy alone; observation cohort (OC) -treated with conventional chemotherapy + gefitinib [24]. The dataset outcomes from this specific investigation indicated that median values for PFS and OS were both extended within the observation cohort in comparison to the control cohort (PFS: eight months in OC versus five months in CC; OS: 24.0 months in OC versus 18.0 months in CC, respectively) [24].…”
Section: Gefitinib Overall Safety Profile/quality-of-life Extensionsupporting
confidence: 90%
See 1 more Smart Citation
“…EGFR is a member of the receptor tyrosine kinase (RTKs), and TKIs, such as gefitinib and erlotinib, have been recommended as the first-line treatment in NSCLC patients with the EGFR mutation. However, acquired resistance occurs after long-term exposure to gefitinib ( 76 ). EMT is a possible mechanism underlying TKI resistance.…”
Section: Overview Of Findingsmentioning
confidence: 99%